2020
DOI: 10.1210/clinem/dgaa001
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytosis and Performance of HbA1c in Detecting Diabetes on an Oxygen-Deficient Plateau: A Population-based Study

Abstract: Context The hemoglobin A1c (HbA1c) test is a standard test for diabetes screening and diagnosis. Objective To evaluate A1c performance for diabetes screening in high-altitude polycythemia compared to a population with a high proportion of people living in an oxygen-deficient environment. Design A population-based epidemiological survey was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…However, concerns about the utility of HbA1c for diagnosing DM and prediabetes have been recently raised ( 21 , 22 ). Many studies have shown frequent discordance between the glucose and HbA1c criteria for diagnosing DM and prediabetes in different populations ( 11 , 13 , 23 26 ), which is consistent with our study. In patients with cystic fibrosis or liver cirrhosis, it is neither accurate nor reliable based on the A1C test ( 13 , 27 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, concerns about the utility of HbA1c for diagnosing DM and prediabetes have been recently raised ( 21 , 22 ). Many studies have shown frequent discordance between the glucose and HbA1c criteria for diagnosing DM and prediabetes in different populations ( 11 , 13 , 23 26 ), which is consistent with our study. In patients with cystic fibrosis or liver cirrhosis, it is neither accurate nor reliable based on the A1C test ( 13 , 27 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…The ADA recommends using HbA1c levels of 5.7% or 6.5% to diagnose prediabetes or diabetes due to its association with retinopathy ( 9 , 10 ). However, variables such as age, ethnicity, and specific clinical conditions that affect hemoglobin glycation rates may impact the accuracy of HbA1c testing ( 11 14 ). Recently, in clinical settings involving patients with obesity, high-altitude polycythemia, liver disease, acute hemorrhage or blood transfusion, numerous articles have indicated that the commonly utilized HbA1c value of 6.5% may result in either underdiagnosis or overdiagnosis of diabetes mellitus ( 13 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cut-off value of HbA1c for diabetes diagnosis among the Tibetan population, which usually had a higher hemoglobin level due to low oxygen adaptation, should be lower than the normal cut-off [ 70 ]. The usage of the identical HbA1c level for diagnosis may lead to an underestimation of diabetes prevalence among Tibetans.…”
Section: Discussionmentioning
confidence: 99%